'Difficulties come to humans and not trees and they need to be faced': A study on resilience among Indian women experiencing intimate partner violence. (November 2014) - Shanthakumari, R Shobitha; Chandra, Prabha S; Riazantseva, Ekaterina; Stewart, Donna E
Background: Not much is known about factors that contribute to resilience among women facing intimate partner violence (IPV), particularly from countries where patriarchy predominates. This qualitative study aimed to gather the perspectives of Indian women self-identified as resilient in the face of IPV and tried to understand the strategies and resources that helped them to maintain or regain resilience. Materials: Data were collected from 16 consenting women who reported IPV and whose husbands were being treated for alcohol problems at a psychiatric centre in Bangalore, India. A semi-structured guided interview format that aimed at understanding factors that enabled them to feel resilient despite IPV in their challenging circumstances was used to gather narratives from the participants. Discussion: Six themes were identified using QSR NVivo software. They were as follows: the support of women, men and family; personal attributes; dignity and work; being strong for the children; and faith in God. Among these women, supportive social networks, personal attributes and aspirations were major clusters contributing to resilience. Conclusion: Attention to these factors may provide an important, strengths-based perspective for interventions to enhance women's resilience when facing IPV.